The new economics of growth : a strategy for India and the developing world - Mellor, John Williams (Ithaca, N.Y. : Cornell University Press, 1976)
This book is largely about the economic factors that determine the choice of a developing strategy.
"A Twentieth Century Fund study."
Includes bibliographical references and index.
oo 08/08/2018
Loans
Keywords: Economic policy; India; Developing countries